Erratum - Bentham Science Publishers (Current Alzheimer Research, 2010)
This is with reference to the article entitled, “Diabetes NEP-Like Endopeptidases and Alzheimer's Disease”, by R.A. Marr and B.J. Spencer, published in Current Alzheimer Research, Vol. 7, No. 3, pp. 223-229. In the article the title was unintentionally published as “Diabetes NEP-Like Endopeptidases and Alzheimer's Disease”. The correct title is “NEP-Like Endopeptidases and Alzheimer's Disease”. The revised title of the article will read as follows: NEP-Like Endopeptidases and Alzheimer's Disease R.A. Marr and B.J. Spencer